‘The Author Makes the Reader Acquainted with His Abode’: Hawthorne as Transatlantic Tour Guide in The Marble Faun and ‘The Old Manse’ - Baraw, Charles (Transatlantic Literature and Author Love in the Nineteenth Century, 2016)
Here the volume continues its reflections on Hawthorne’s career but turns to his place in the literature of ‘homes and haunts’, taking up the question of how literary geography and its localization of authors helped construct an authorial presence for Americans and a tangible transatlantic literary canon. (It turns out that having a home on the literary itinerary was crucial to nineteenth-century reception.) Baraw demonstrates that the poetics of literary tourism provided Hawthorne with both a means of self-canonization as a tourist attraction and a tool for cultivating the ideal ‘English’ reader for his books. This essay begins a strand of chapters related to literary tourism and the construction of international heritage landscapes.
Citation Key Alias: lens.org/027-169-429-746-184
Keywords: American Author; Authorial Persona; Direct Address; Tour Guide; Tourist Attraction; dept.eng